Classroom Management Strategies of Teachers in Selected Public Elementary Schools - Salgo, Fressia Azalea (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the extent of utilization of classroom management strategies among teachers in selected public elementary schools in Morong District, Division of Rizal, during School Year 2025–2026. Using a descriptive survey research design, data were gathered from a total population of 195 public elementary school teachers from Bombongan, Calero-Lanang, Caniogan, Lagundi, Maybancal, Talaga, Timoteo A. Reyes Memorial, and Tomas Claudio Memorial Elementary Schools. Respondents were profiled in terms of age, sex, civil status, educational attainment, length of service, position title, and in-service trainings attended. A researcher-made questionnaire checklist was used to assess the extent of utilization of classroom management strategies in terms of motivational, instructional, and evaluative strategies. Documentary analysis of teachers’ Individual Performance Commitment and Review (IPCR) was also conducted to determine their level of work performance.Findings revealed that most respondents were 36–39 years old, female, married, Bachelor’s degree holders, with 10–14 years of teaching experience, holding Teacher I positions, and having attended school-based in-service trainings. Teachers consistently utilized classroom management strategies across motivational, instructional, and evaluative domains. No significant differences were found in the extent of utilization when grouped according to age, sex, civil status, position title, length of service, and in-service trainings; however, educational attainment showed a significant difference. Teachers were rated as very satisfactory in their work performance, with no significant relationship between the extent of utilization of classroom management strategies and performance levels.The study concludes that demographic factors such as age, sex, civil status, position, length of service, and training are not predictors of classroom management strategy utilization, while educational attainment is a significant predictor. Furthermore, classroom management strategies are not determinants of teachers’ performance. It is recommended that administrators promote higher education, strengthen professional development programs, and provide continuous support to enhance classroom management practices.
Keywords: Classroom Management, Teaching Strategies, Teacher Performance, Public Elementary Schools, Educational Attainment